How Useful Was That Critical Reflection? Technology Enhanced Learning in Physiology Skill Lab - Malik, Samina (The FASEB journal, 2022)
Critical reflection blended with technology is essential to gain insight into one's action leading to enhanced learning & performance in Objectively Structured Clinical Evaluation (OSCE). However, it is still being under-utilized by teachers and students in most second year undergraduate clinical physiology curricula of Pakistan including University College of Medicine and Dentistry. To evaluate the usefulness of critical reflection blended with technology as a learning enhancement tool. Teachers and second year physiology students of University College of Medicine and Dentistry, University of Lahore mutually planned an experimental study of QUAL-quan design, using critical reflection as a tool to enhance learning and performance in cranial nerve examination. The technological stimulus or intervention involved student engagement by video-presentation of role-play conducted by class-fellows on cranial nerves examination. Each of the three randomized groups (n=50) experienced conventional practical demonstration by a standardized common demonstrator followed by hands-on-practice by common tutors. Group B was additionally involved in video recording of role-play, with one student as examiner, second student as a subject, and the third as the examiner who marked the structured key. The remaining students observed the entire activity. Group C additionally watched recorded video followed by reflective group discussion analyzing examination against structured key and tutor's performance and corrected the mistakes presented in the video through critique and collaborative feedback. Open and closed ended feedback was obtained from students and tutors. Qualitative analysis was conducted on piloted and peer-reviewed feedback questionnaires whereas quantitative analysis was done on surprise formative assessment scores after couple of months to see the behavioral change as per Kirkpatrick's model. Comparatively significant quantitative and qualitative responses were obtained from group C on ANOVA, including enjoyable learning environment, enhanced memory, critical thinking, clarity of concepts, time-management & confident performance. Critical reflection blended with technology may enhance learning and performance.